2016
DOI: 10.1039/c6nj00079g
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective organocatalysis using SOMO activation

Abstract: Enantioselective organo-SOMO activation enables radical based functionalization of carbonyl compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 34 publications
1
26
0
2
Order By: Relevance
“…The amine catalyst is finely tuned so that only the si face of this radical cation is exposed for potential reaction with a SOMO nucleophile, e.g., allylsilane 37 , thus providing a high level of enantiocontrol. In addition to enantioselective allylation, a panel of other transformations 38 such as vinylation 39 , arylation 40 , alkynylation 41 , and alkylation 42 , 43 reactions have been also established. Besides, the SOMO activation strategy has been extended to the γ-alkylation of enal via a dienamine intermediate formed by condensation with proline-derived catalyst 5 .…”
Section: Introductionmentioning
confidence: 99%
“…The amine catalyst is finely tuned so that only the si face of this radical cation is exposed for potential reaction with a SOMO nucleophile, e.g., allylsilane 37 , thus providing a high level of enantiocontrol. In addition to enantioselective allylation, a panel of other transformations 38 such as vinylation 39 , arylation 40 , alkynylation 41 , and alkylation 42 , 43 reactions have been also established. Besides, the SOMO activation strategy has been extended to the γ-alkylation of enal via a dienamine intermediate formed by condensation with proline-derived catalyst 5 .…”
Section: Introductionmentioning
confidence: 99%
“…This strategy might provide a solution for the synthesis of vinyl sulfides by the cross-coupling of an alkene radical and a thiyl radical. It has been reported that an enamine can generate the enamine radical cation under oxidation and/or transition-metal catalyst conditions 6. And thiophenol can produce the thiyl radical which might couple with the enamine radical cation to furnish the vinyl sulfide.…”
Section: Introductionmentioning
confidence: 99%
“…9 (ref. [62][63][64] would form a radical cation that could add to the alkene of allylic alcohol 64, thus promoting the ring-enlargement rearrangement. A broad range of enantioenriched a-quaternary cyclopentanones can be accessed using this method.…”
Section: Allylic Alcoholsmentioning
confidence: 99%